Analisis Penerapan Sistem Akuntansi Penerimaan dan Pengeluaran Kas pada PT X - Rosa Amalia Rizki; Nanda Wahyu Indah Kirana (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
PT X is a company in the field of national project construction. PT X's operational activities are sales of goods and installation services. The method used is descriptive qualitative. Cash receipts by PT X begin with the receipt of purchases of goods by the cashier which will then be submitted to the sales department to be recorded. The sales department will submit to the warehouse department. While cash disbursements begin with employees submitting checks as proof of expenditure to the cashier and then will be processed by the accounting staff. PT X's cash receipt accounting system is in accordance with the theory that requires cash receipts to have sales functions, cash functions, shipping functions, and accounting functions in them. In addition, PT X's cash disbursements are also in accordance with the theory that requires cash disbursements to have cash functions and accounting functions in them.